Factors That Influence Non-Motor Impairment Across the ALS-FTD Spectrum: Impact of Phenotype, Sex, Age, Onset and Disease Stage - Devenney, Emma M.; McErlean, Kate; Tse, Nga Yan; Caga, Jashelle; Dharmadasa, Thanuja; Huynh, William; Mahoney, Colin J.; Zoing, Margaret; Mazumder, Srestha; Dobson-Stone, Carol; Kwok, John B.; Halliday, Glenda M.; et al. (Frontiers in Neurology, 2021)
Objective: This study aimed to establish (1) the pattern and severity of neuropsychiatric symptoms and other non-motor symptoms of sleep and mood, across ALS phenotypes in comparison to bvFTD and (2) the contribution of non-modifiable factors including age, sex and disease state to the severity of symptoms experienced by ALS patients. Methods: Consecutive participants were recruited to the study and underwent a detailed clinical, cognitive, behavioral and neuroimaging assessment. Neuropsychiatric and other non-motor symptoms were determined using the Cambridge Behavioral Inventory, the CBI-R. The scores were converted to define impairment in terms of mild, moderate and severe symptoms for each subscale. Rate, severity and contribution of King's staging and modifiable factors were also determined and a regression model identified predictors of symptom severity. Results: In total, 250 participants (115 ALS, 98 bvFTD, and 37 ALS-FTD patients) were recruited. A similar pattern of neuropsychiatric symptom severity was identified (apathy, disinhibition and stereotypic behavior) for all behavioral phenotypes of ALS compared to bvFTD (all p > 0.05). Neuropsychiatric symptoms were also present in cases defined as ALSpure and the cognitive phenotype of ALS (ALSci) although they occurred less frequently and were at the milder end of the spectrum. Disordered sleep and disrupted mood were common across all phenotypes (all p < 0.05). The severity of sleep dysfunction was influenced by both sex and age (all p < 0.05). Neuropsychiatric symptoms, sleep and mood disorders were common early in the disease process and deteriorated in line with progression on the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised (ALSFRS-R; all p < 0.05). Diagnostic phenotype, disease duration and global cognition scores were the strongest predictors of non-motor and neuropsychiatric impairments. Conclusion: The current findings reveal strikingly similar patterns of changes across the subgroups of ALS and bvFTD, supporting the concept of the ALS-FTD spectrum. The findings further highlight the impact of non-motor and neuropsychiatric symptoms in patients with ALS, that are often as severe as that seen in ALS-FTD and bvFTD. This study advances understanding across the ALS-FTD spectrum that may accelerate the early identification of patient needs, to ensure prompt recognition of symptoms and thereby to improve clinical awareness, patient care and management.